2019
DOI: 10.1111/rge.12219
|View full text |Cite
|
Sign up to set email alerts
|

Age and Tectonic Setting of Mesothermal Magmatic Hydrothermal Vein‐Type Pb–Zn–(Ag) Mineralization in the Xiaohongshilazi Deposit, Central Jilin Province, Northeast China

Abstract: The Xiaohongshilazi deposit located in central Jilin Province, Northeast China, is a newly discovered and medium‐scale Pb–Zn–(Ag) deposit with ore reserves of 34,968 t Pb, 100,150 t Zn, and 158 t Ag. Two‐stage mineralization has been identified in this deposit. Stratiform volcanic‐associated massive sulfide (VMS) Pb–Zn mineralization interbedding with the marine volcanic rocks of the Late Carboniferous–Early Permian Daheshen Formation was controlled by the premineralization E–W‐trending faults. Vein‐type Pb–Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Nevertheless, the volcanic rocks from the Daheshen Formation were spatially, temporally, and genetically related to the layered Pb-Zn mineralization, which is evidenced by the following: (1) Dacite samples of the Daheshen Formation from Dongfeng and Xifeng mine in the Xiaohongshilazi ore district were all interbedded with the layered orebodies (Figures 2B and 4A). ( 2) The volcanic rocks from the Daheshen Formation and the layered orebodies were overlain by the volcanic rocks from the Sihetun Formation (~225Ma), and both of them were cut by the vein-type Pb-Zn-(Ag) orebodies and the granodiorite porphyry (~200Ma) (Figure 2A) [20]. (3) No Pb-Zn mineralization was found in the rhyolite and andesite from the Sihetun Formation (Figure 3A-F).…”
Section: Age Of Magmatic Hydrothermal Events and Layered Pb-zn Minera...mentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, the volcanic rocks from the Daheshen Formation were spatially, temporally, and genetically related to the layered Pb-Zn mineralization, which is evidenced by the following: (1) Dacite samples of the Daheshen Formation from Dongfeng and Xifeng mine in the Xiaohongshilazi ore district were all interbedded with the layered orebodies (Figures 2B and 4A). ( 2) The volcanic rocks from the Daheshen Formation and the layered orebodies were overlain by the volcanic rocks from the Sihetun Formation (~225Ma), and both of them were cut by the vein-type Pb-Zn-(Ag) orebodies and the granodiorite porphyry (~200Ma) (Figure 2A) [20]. (3) No Pb-Zn mineralization was found in the rhyolite and andesite from the Sihetun Formation (Figure 3A-F).…”
Section: Age Of Magmatic Hydrothermal Events and Layered Pb-zn Minera...mentioning
confidence: 99%
“…In light of the research of the vein-type Pb-Zn-(Ag) mineralization in the Xiaohongshilazi deposit (~200 Ma) [20], it can be concluded that there were three stages of tectonomagmatic-hydrothermal events that occurred in the Xiaohongshilazi area from the early Permian to the early Jurassic: (1) the early Permian (~278 Ma) forming of the Daheshen Formation marine volcanic rocks related to the layered Pb-Zn mineralization; (2) the late Triassic (~225 Ma) forming of the Sihetun Formation volcanic rocks and the diorite porphyry dikes; (3) the early Jurassic (~200 Ma) forming of the granodiorite porphyry associated with the vein-type Pb-Zn-(Ag) mineralization.…”
Section: Age Of Magmatic Hydrothermal Events and Layered Pb-zn Minera...mentioning
confidence: 99%
See 3 more Smart Citations